Bioreactors : design, operation and novel applications - Mandenius, Carl-Fredrik, 1954- (Wiley-VCH Verlag GmbH & Co., 2016)
In this expert handbook both the topics and contributors are selected so as to provide an authoritative view of possible applications for this new technology. The result is an up-to-date survey of current challenges and opportunities in the design and operation of bioreactors for high-value products in the biomedical and chemical industries.